ChemInform Abstract: Hypervalent‐Iodine‐Mediated Synthesis of 1, 2‐Dispirodienones: Experimental and Theoretical Investigations. Issue 14 (March 2016) - Hromjakova, Tatiana; Retailleau, Pascal; Grimaud, Laurence; Gandon, Vincent; Chabaud, Laurent; Guillou, Catherine
Abstract: The oxidation of phenol acetanilides involves the formation of a carbocationic species leading to either [6, 5, 6] tricyclic title dispirodienones (most cases) or a [6, 6, 6] tricyclic aryl spirodienone (some cases, depending on the substituents on the phenol acetanilide and the reaction conditions).